Wind Identification of Spinning Projectile Using Improved Multiobjective Differential Evolution Algorithm - Dingye Zhang; Jun Guan; Wenjun Yi; Youran Xia; Kangjian Wang (International Journal of Aerospace Engineering)
Wind velocity has an important influence on the ballistic characteristics of uncontrolled projectiles. It is difficult to precisely determine the projectile’s impact position if wind velocity information from the projectile’s flight process cannot be collected. A wind velocity identification technique of spinning projectile based on the multiobjective chaotic adaptive differential evolution algorithm is suggested to increase the estimation accuracy of wind velocity and ballistic prediction accuracy during projectile flight. The variation law of projectile aerodynamic characteristics under no wind situation is calculated using the 4D kinematic model of spinning projectile. Three aerodynamic parameter coefficients are chosen as reference variables, three objective functions are defined by mean square error, and the two components of wind velocity along the ground coordinate system are used as decision variables in the identification process. The study identifies the two components, which is based on the multiobjective chaotic adaptive differential evolution algorithm. Several groups of wind velocity identification under constant and variable wind conditions are numerically simulated. The results show that the suggested method can estimate wind velocity effectively and precisely throughout the flight of spinning projectile.